P22-S Is dry eye related with central excitability changes?. Issue 7 (July 2019) - Kızıltan, Meral; Doğan, Cezmi; Ayas, Selahattin; Gunduz, Ass. Aysegul
Abstract : Background: We hypothesized that there may be adaptive changes in the central pathways in patients with dry eye. To delineate this issue, we aimed to analyze blink reflex (BR), prepulse inhibition (PPI) of BR, recovery excitability of BR (BR-RC), and somatosensory temporal discrimination threshold (STDT). Method: We included 17 patients with dry eye between September 2018 and November 2018. We also formed a control group composed of 14 healthy subjects with similar age and gender. After clinical evaluation, we recorded BR, PPI of BR (with 50 and 100 ms intervals), BR-RC (300 and 500 ms intervals) and we determined STDT over second finger. Results: None of the patients had any spasm activity. The disease duration was between 2 and 15 years. There was a R2-PPI deficit at each interval in the patient group compared to healthy subjects. The recovery ratios at 500 ms were higher in patients compared to healthy subjects. STDT was abnormally high in patients than healthy subjects ( p  = 0.000) despite the similar sensory threshold in both groups. Discussion: Although the cohort in this study did not have any involuntary spasms, they exhibited inhibitory deficit, increased recovery excitability and abnormal STDT similar to that found in blepharospasm. Most of the patients in this cohort have been in follow-up for a long period and they did not develop any spasThus, we suggest patients with dry eye exhibit central adaptive changes.